The Dynamics Of Theoretical Approaches In Contemporary Public Administration Studies: Critical Analysis And Policy Implications - Nurman, Nurman; Zainal, Zainal; Ardianyah, Ardiansyah (UIR Press, 2024)
Public administration serves as a central pillar in the governance system, responsible for designing, implementing, and evaluating public policies. In the modern context, public administration has undergone significant transformation in response to the ever-evolving dynamics of social, political, economic, and technological developments. Globalization and digitalization, as well as the complexity of public problems, demand a more adaptive, innovative, and evidence-based public administration system. Research methodology plays an important role in determining the validity and reliability of scientific findings in public administration studies. Choosing the right method not only ensures the accuracy of the data collected but also increases the relevance of the analysis in answering research questions. In this context, a qualitative approach with descriptive and exploratory analysis was chosen to understand the concepts, patterns, and dynamics of the evolution of public administration theory in facing contemporary challenges. Critical Analysis of Contemporary Approaches in Public Administration. The evolution of public administration theory has been marked by a series of paradigms, each contributing unique insights into governance and service delivery. The Classical Public Administration (CPA) model, rooted in Max Weber's bureaucratic principles, emphasizes hierarchical organization, rule-based efficiency, and accountability. Impact of Theoretical Approaches on Policy Effectiveness and Governance. The impact of theoretical approaches on policy effectiveness and governance is profound, as these frameworks shape administrative structures, decision-making processes, and citizen engagement. Conclusion this study confirms that theoretical approaches in public administration continue to experience dynamic developments along with social, political, economic, and technological changes.